The Independence of the Judiciary: an Assessment of the Reality of the Constitutional Doctrine in Uganda - Ssensikombi, Alexander (Available at SSRN 2984300., 2017)
This paper seeks to discuss the Constitutional doctrine of the Independence of the Judiciary as enshrined in Article 128 of the Constitution of the Republic of Uganda (as amended); its safeguards and also gives an assessment of the applicability of this doctrine in Uganda; thereafter making recommendations
Keywords: Constitutional Law, Judicial Independence, Independence of the Judiciary, Rule of Law, Democracy